The intensity of sexual selection, body size and reproductive success in a mating system with male–male combat: is bigger better?. Issue 7 (23rd March 2020) - Glaudas, Xavier; Rice, Stephen E.; Clark, Rulon W.; Alexander, Graham J.
Abstract : Body size is a key selected trait in many animal systems: larger size is sexually selected for in males because it confers a reproductive advantage during contest competition for access to females, and larger females are naturally selected for fecundity. Herein, we used radio‐telemetry to gather a large dataset of male–female interactions and DNA paternity analyses to characterize the intensity of sexual selection and the link between two body size metrics (body length and condition, the latter manipulated experimentally for males) and reproductive success in a population of puff adders Bitis arietans . Our multiple estimates of the intensity of sexual selection generally indicated that males experienced stronger sexual selection than females. However, the Bateman gradients did not differ by sex, despite the fact that males increased reproductive success by mating with multiple females while females did not. We also found no strong evidence that females experienced indirect fitness benefits through multiple matings. Body size was not a key predictor of male reproductive success, and for females, body condition – but not body length – was the critical fecundity trait. Altogether, a combination of factors suggests that post‐copulatory mechanisms of sexual selection (e.g. sperm competition, cryptic female choice) may play critical roles in this mating system and perhaps that of other snakes. We interpret our findings in the context of sexual conflict – a ubiquitous and potent driver of mating strategy evolution – to propose a scenario for the evolution of female promiscuity that is applicable to many other animal systems where males roam widely to locate females at high costs.